Diagnostic value of cerebrospinal fluid levels of D-lactate, tumour necrosis factor-alpha and interleukin-6, -8, and -17 in suspected nosocomial meningitis - Sibel Yorulmaz Goktas; Arzu Yılmaztepe Oral; Emel Yılmaz; Emin Halis Akalın; Furkan Guvenc; Guven Ozkaya; Hasan Kocaeli; Seref Dogan; Selcuk Yılmazlar; Haluk Barbaros Oral (Singapore Medical Journal)
Introduction: This study aimed to determine the diagnostic value of interleukin (IL)-6, IL-8, IL-17, tumour necrosis factor-alpha (TNF-α) and D-lactate levels in the cerebrospinal fluid (CSF) of nosocomial meningitis patients. Methods: The CSF levels of cytokines and D-lactate were compared across 29 episodes of nosocomial meningitis, 38 episodes of pleocytosis (without meningitis) and 54 control subjects. Results: The CSF levels of IL-6, IL-8, and D-lactate were higher in the group with nosocomial meningitis compared to the control group and the group with pleocytosis without meningitis (P < 0.05). For IL-6 levels (threshold: >440 pg/mL), the sensitivity and specificity were 55.17% and 94.74%, respectively. For IL-8 levels (threshold: >1,249 pg/mL), the sensitivity and specificity were 44.83% and 84.21%, respectively. In patients with nosocomial meningitis, when the threshold of D-lactate levels was >1.05 μmol/mL, the sensitivity and specificity were 75.86% and 63.16%, respectively. In pleocytosis (without meningitis) CSF samples and in nosocomial meningitis CSF samples, the highest area under the receiver operating characteristic curve (AUC) was calculated for triple combination model of IL-6, IL-8 and D-lactate levels (AUC 0.801, P < 0.001) and double combination model of IL-6 and IL-8 (AUC 0.790, P < 0.001). Conclusion: Our study findings suggest that IL-6, IL-8 and D-lactate levels could be diagnostic markers for nosocomial meningitis.